Enhanced thermoelectric efficiency of the bulk composites consisting of "Bi2Te3 matrix" and "filler Ni@NiTe2 inclusions". (15th March 2021) - Yaprintsev, Maxim; Vasil'ev, Alexei; Ivanov, Oleg; Zhezhu, Marina; Yaprintseva, Ekaterina; Novikov, Vseslav
Abstract: Mixture of thermoelectric Bi2 Te3 and ferromagnetic Ni powders was spark-plasma-sintered to prepare bulk composites with different Ni content (0.5 and 1.25 at.%). Hexagonal Bi2 Te3, cubic Ni and trigonal NiTe2 phases coexist in the composites. The Bi2 Te3 phase forms matrix of the composite, whereas the Ni and NiTe2 phases corresponds to filler. The filler is formed by Ni@NiTe2 ("core-shell") inclusions. Forming "core-shell" inclusions is due to high-temperature diffuse redistribution of Ni during the composites sintering. Gradient distributions of Ni, Te and Bi exist within these inclusions. Embedding the Ni filler into the Bi2 Te3 matrix lead to drastic decrease of electrical resistivity, decrease of Seebeck coefficient, and increase of thermal conductivity. As result, the composites demonstrate enhanced thermoelectric efficiency. Optimal combination of thermoelectric properties for the composite with x = 0.5 at.% leads to more than two-fold enhancement of the thermoelectric figure-of-merit (∼0.67 for the composite against ∼0.30 for reference Bi2 Te3 sample). Graphical abstract: Image, graphical abstract BSE image of the filler Ni@NiTe2 inclusion